Population of Gubin District in the Context of Situational and Statistical Reports in the Years 1945–1949 - Hanna Kurowska (Przeszłość Demograficzna Polski, 2020)
The article aims to reconstruct the number of inhabitants in the Gubin district in the early post-war years. The statistical data available include previously unused source material in the form of reports and lists of the district administrator and the State Repatriation Office (PUR). The displacement of Germans and the influx of Poles will be discussed, the district’s population levels will be given with a division into town and village, and the speed of change in 1945–1949 will be indicated, as well as the population structure in terms of sex, age, nationality and direction of influx (repatriates from the East and West and displaced people from central Poland).